Sister Boniface mysteries. Season one [videorecording (DVD)] - Tindall, Jude; Watson, Lorna; Brown, Max, 1981-; Iwu, Jerry; Raison, Miranda, 1980- (BBC, 2022)
From the makers of Father Brown and Shakespeare and Hathaway, Private Investigators comes a light-hearted murder mystery series. It's the 1960s and police forensics are rudimentary. Luckily the residents of Great Slaughter, nestled deep in the British countryside, have a secret weapon. Sister Boniface. This nun might be predisposed to forgive but she's also one hell of an amateur detective. If there's evidence to be found, Boniface will find it, with a little help from dashing maverick DI Sam Gillespie and buttoned-up Bermudan Ds Felix Livingstone, who's horrified to be stuck in the eccentric world of Great Slaughter. A corpse is found stuffed inside a dummy at the local fair; tragedy hits a visiting TV crew, and a gruesome discovery is made in Edie's beloved allotment plot. It's down to Siste Boniface, and a few hasty Hail Marys, to save the day.